LUX ARRHYTHMO Interacts With ELF3a and ELF4a to Coordinate Vegetative Growth and Photoperiodic Flowering in Rice - Cai, Zhengzheng; Zhang, Yudan; Tang, Weiqi; Chen, Xuequn; Lin, Chenchen; Liu, Yang; Ye, Yanfang; Wu, Weiren; Duan, Yuanlin (Frontiers in Plant Science, 2022)
The evening complex (EC) plays critical role in photoperiod flowering in Arabidopsis. Nevertheless, the underlying functions of individual components and coordinate regulation mechanism of EC genes in rice flowering remain to be elucidated. Here, we characterized the critical role of LUX ARRHYTHMO (LUX) in photoperiod perception and coordinating vegetative growth and flowering in rice. Nonfunctional alleles of OsLUX extremely extended vegetative phase, leading to photoperiod-insensitive late-flowering and great increase of grain yield. OsLUX displayed an obvious diurnal rhythm expression with the peak at dusk, and promoted rice flowering via coordinating the expression of genes associated with the circadian clock and the output integrators of photoperiodic flowering. OsLUX combined with OsELF4a and OsELF3a or OsELF3b to form two ECs, of which the OsLUX-OsELF3a-OsELF4a was likely the dominant promoter for photoperiodic flowering. In addition, OsELF4a was also essential for promoting rice flowering. Unlike OsLUX, loss OsELF4a displayed a marginal influence under short-day (SD) condition, but markedly delayed flowering time under long-day (LD) condition. These results suggest that rice EC genes share the function of promoting flowering. This is agreement with the orthologs of SD plant, but opposite to the counterparts of LD species. Taken together, rice EC genes displays similar but not identical function in photoperiodic flowering, probably through regulating gene expression cooperative and independent. These findings facilitate our understanding of photoperiodic flowering in plants, especially the SD crops.